Numeric oscillations decreasing in electromagnetic transient simulations due to the variation of the circuit quantity used for the transmission line representation - Lessa, Leonardo S. [UNESP]; Prado, Afonso J. [UNESP]; Kurokawa, Sérgio [UNESP]; Filho, José Pissolato [UNESP]; Bovolato, Luiz F. [UNESP] (ACTA Press, 2011)
Studies of electromagnetic transients in transmission lines are greatly important for several analyses related to the power systems. Introducing these studies for undergraduate students, in this paper, it is presented an investigation about the limitations of the π circuit application for the transmission line representation. This investigation is carried out by Electrical Engineering undergraduate students and its main objective is to obtain a numeric tool for the initial analyses of the electromagnetic transients by undergraduate students where it is possible a great variation in the quantity of applied π circuits. Using this great variation, it is checked the influence of the quantity of π circuits in the decreasing of numeric oscillations that are observed in the obtained results.
Keywords: π circuit; Electromagnetic transient; EMTP; Mathematical model; Numeric method; Simulation; Transmission lines; Wave traveling